Synthesis of calcium ferrite photocatalyst for the COD photodegradation of palm oil mill effluent under visible light - Benedict, Ashwin Charles (2020)
Malaysia has long battled with the issue of palm oil mill effluent (POME) pollution which has proven to be detrimental to the environment. Although some attempts to alleviate this problem using ZnO and TiO2 photocatalysts under ultra-violet irradiation have been undertaken, these have shown significant room for improvement. The low light utilization as well and mediocre photodegradation efficiency produced by these two systems highlight the need for a visible light driven photocatalyst as a long term solution to the problem. This thesis explores the application of CaFe2O4 as a visible light driven photocatalyst towards addressing that problem. Two synthesis routes namely the auto-combustion (AC) and co-precipitation (CP) routes and two calcination temperatures (550 °C and 700 °C) were used to produce a total of four CaFe2O4 catalysts namely AC550, AC700, CP550 and CP700. CP550 exhibited the greatest chemical oxygen demand (COD) degradation of 69% at a 0.75 g/L catalyst loading and an oxygen flow rate of 60 ml min-1 after 8 h of irradiation. The reaction adhered well to first order kinetics with a rate constant of 2.7 x 10-5 min-1. Nitrogen physisorption studies indicated CP550 had the highest Brunauer-Emmett-Teller (BET) specific surface area (27.28 m2/g) and pore volume (0.077 cm3/g) of the prepared photocatalysts which dropped precipitously for CP700 upon increasing the calcination temperature to BET specific surface area of 9.73 m2/g and pore volume of 0.025 cm3/g due to annealing which created a smoother surface area as evidenced by the scanning electron microscope (SEM) images. Ultraviolet-visible diffuse reflectance spectroscopy (UV-Vis DRS) indicated CP550 had the highest band-gap (1.52 eV) which is likely due to the presence of CaFe5O7 which is a unique structure of CaFe2O4 containing three units of FeO in a stable phase as deduced from the energy dispersive X-ray microanalysis (EDX) data and confirmed by X-ray diffraction (XRD) peaks. CP550 also displayed the lowest photoluminescence (PL) spectra of the as prepared photocatalysts indicating a low electron-hole recombination rate. A scavenging study using iso-propyl alcohol (IPA) caused a severe drop in COD degradation from 69% to just 7% indicating hydroxyl radicals as the main reactive oxidative species. The recyclability study indicated that reusing the spent catalysts led to a decrease from 69.0% to 65.0% and finally 61.0% on subsequent cycles indicating some loss of activity over time. Post reaction characterization of the spent catalyst indicated that the loss of activity was due to carbon deposition as evidenced by FTIR and EDX data. This research contributes to the body of knowledge addressing the issue of visible light driven photocatalysis for the amelioration of recalcitrant environmental pollutants such as POME.